Criminal Liability for the Creation and Distribution of Deepfake Pornographic Videos on Social Media - Ruben Nicholas Alfredo Tobing; Yuliana Yuli (Green Publisher Indonesia, 2026)
The advancement of information technology, particularly artificial intelligence, has significantly influenced various aspects of human life while simultaneously giving rise to new forms of cybercrime, including the misuse of deepfake technology. Deepfake technology is frequently exploited to create and disseminate pornographic content on social media platforms, resulting in serious violations of victims’ privacy, dignity, and psychological well-being. This study examines criminal liability for the creation and distribution of deepfake-based pornographic content under Law Number 44 of 2008 on Pornography and Law Number 19 of 2016 on Electronic Information and Transactions, as well as the challenges faced in law enforcement. This research adopts a normative legal research method using statutory and conceptual approaches, supported by library research on relevant legislation and legal doctrines. The findings reveal that current legal regulations in Indonesia have not explicitly addressed deepfake technology, leading to difficulties in legal qualification, evidence gathering, and effective law enforcement. Therefore, this study emphasizes the urgency of strengthening and updating legal frameworks to ensure legal certainty and provide comprehensive protection for victims of deepfake-related crimes.